Indian Herbal Plants: Efficacious Restorative Potential in Hyperglycemia - Rekha, Kumari (Recent Progress in Plant and Soil Research Vol. 4, 2021)
Objective: The focus of research was to explore the efficacy of Syzigium cumuni seeds on the diabetes and their potential on male reproductive physiology and histopathology of Swiss albino mice (Mus musculus), besides various Indian herbal plants present in amelioration of various complications of hyperglycemia, especially in India. In my experimental work diabetic condition was instigated in male Swiss albino by injecting Alloxan monohydrate. Fixed dose of Syzigium cumuni seeds powder along with food were fed to assess their restorative potential. Hyperglycemia is a complicative human ailment afflicting many from various walks of life in different countries. Hyperglycemia is a metabolic disorder characterized by high blood sugar level over a prolonged period. Symptoms include frequent urination, increased thirst, increased appetite. It is due to either the pancreas not produces enough insulin or the cells of body do not respond properly to the insulin. Major long term complications relate to damage to blood vessels, cardiovascular disease, damage to the eyes (retinopathy), damage to kidneys (nephropathy). Though there are various approaches to reduce its ill effect and its complications, herbal medications are preferred due to its low cost, easy availability and no side effect at all. A list of medicinal plants with proven antihyperglycemic properties are in practice in amelioration of hyperglycemia. These include babul (Acacia Arabica),neem (Azadirachta indica), gurhal (Hibiscus rosa-sinesis), bitter gourd (Momordica charantia),giloy (Tinospora cordifolia), methi (Trigonella foenum-graecum) and jamun (Syzigium cumuni). Syzigium cumuni commonly known as jamun, jambul, black plum, Indian black berry belong to family Myrtaceae. Fruit has attractive colour,due to presence of anthocyanin especially in its peel parts. The berries contain only one seed. Syzigium cumuni is one of the widely used medicinal plants in the treatment of diabetes and several other diseases. The plant is rich in compounds containing anthocyanins, glucoside, ellagic acid, isoquercetin, kaempferol, myricetin, and hydrolysable tannins (1-0-galloyl castalagin and casuarinin). The seeds also contain alkaloid jambosine and glycoside jamboline, which slows down the diastatic conversion of starch into sugar. Addition of ethanolic extract of seeds and seed powder of Syzigium cumuni in alloxan- induced diabetic rats showed significant reduction in blood sugar level and enhancement in the histopathology of pancreatic islets. Decrease in glycosuria and blood urea levels has also been reported.Seeds contain glucoside jamboline, a phenolic substance,a trace of pale yellow essential oil, chlorophyll, fat, resin, albumin ,tannins (19%), Phenolic compounds such as ellagic acid, gallic acid (1-2%), caffeic and ferulic acids and its derivatives such as guaicol, resorcinol dimethyl ether and corilaginin. The seeds are fairly rich in protein and calcium. Monoterpenoids like \(β\)-pinene, \(α\)-terpinene, terpinolene, borbeneol, \(β\)-phellandrene, a-terpineol and eugenol and flavonoid such as rutin, quercetin. B-sitosterol are also present in Syzigium cumuni (Black Plum seed). Findings: The Syzigium cumuni (Black Plum) seed powder stimulates the secretion of pancreatic insulin which restores histoarchitecture of pancreatic \(β\)-cells in the experimental animal cells indicating its antidiabetic or antihyperglycemic property. Various phytochemicals like triterpenes, anthocyanin, oleic acid, essential oils, glycosides, saponins and several members of Flavonoids which directly or indirectly affects insulin resistancy and \(β\)-cells function, is also present in its seed. Novelty: Identification of such active compounds is a great potential in producing safer drugs for the treatment of various ailments including diabetes. Although most of studies of Syzigium cumuni as an antidiabetic emissary with its possible implemented actions and complications of diabetes like cataract, neuropathy, nephropathy have been conduced but detailed research on isolation of bioactives through clinical try-out followed by standardization is seriously required to know the prospectives of the plant. Presence of different identified phytochemicals in Syzigium cumuni (Black Plum) seed with their reported mechanisms of action shows that some compounds target multiple metabolic routes, thereby, becoming a potential therapeutic tool .